If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10y + -6 = 7y + 3 Reorder the terms: -6 + 10y = 7y + 3 Reorder the terms: -6 + 10y = 3 + 7y Solving -6 + 10y = 3 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. -6 + 10y + -7y = 3 + 7y + -7y Combine like terms: 10y + -7y = 3y -6 + 3y = 3 + 7y + -7y Combine like terms: 7y + -7y = 0 -6 + 3y = 3 + 0 -6 + 3y = 3 Add '6' to each side of the equation. -6 + 6 + 3y = 3 + 6 Combine like terms: -6 + 6 = 0 0 + 3y = 3 + 6 3y = 3 + 6 Combine like terms: 3 + 6 = 9 3y = 9 Divide each side by '3'. y = 3 Simplifying y = 3
| 9x+7=2x-5 | | 7p+4=-p+9+2+3p | | 1/2x-4=17 | | 8-2y+2y+3=3 | | 4y=2(2+12) | | 5(k+5)=-7 | | 4x^5-x^3-240=0 | | 3.52=2.552-4.25+6.25 | | .2847x+30000000=x | | -8=1(-9t+27) | | 4X+10+175-2x=180 | | -8=1(-9+27) | | 1.2x^2+.4x=.50 | | (64n^12)^-1/6 | | 4x=1/1024 | | 4x=3(x+3)+4 | | 8t-40=12t+30-10 | | 2z-2=-14+6z | | 6t-14=13+9t | | 2(3+4x)-5=25 | | 3x-23=2x-14 | | 3x+4=4(X-3) | | 5/9=10/x | | .25x+20=50 | | 3y^2-y=equation | | 3y^2-y= | | 12x^4-60x^2-432=0 | | 120=10x+10 | | 1/3b-25 | | 65x=110x | | 12x+y=59 | | 10+7x=21-4x |